Pozzolanic and strength properties of mortar containing chemically pre-treated coal bottom ash - Rahimah, Embong (2019)
An intensive research to produce highly reactive pozzolan, particularly from industrial waste, to replace the role of cement in construction material is crucial. This action would increase the recycling rate of industrial waste and, concurrently, reduce the extraction of non-renewable resources of limestone. Unique characteristic of coal bottom ash as one of the industrial based pozzolan gained less popularity because of its low reactivity and heavy metal leaching due to conventional method used for disposal. Few researches are available in the use of coal bottom ash as an alternative pozzolan. Most of the literatures discussed the functionality of it as an aggregate. Therefore, an alternative approach was deliberated in this research to safely utilized coal bottom ash by eliminate risk of leaching and enhance the quality of bottom ash as pozzolanic purpose. Pre-treatment with acid solution at various parameters was used to reduce deleterious material and impurities from the coal ash. The process begun with soaking of ash in various concentration of acid solutions with different time interval and left dried in an oven at 105ºC overnight. Coal bottom ash after the pre-treatment with optimum parameter was then undergo solutiongelification process with various alkali based solution for 2 hours soaking durations. The ash obtained was then characterized by determining its chemical oxides composition, particle size analysis, mineralogical characteristics and microstructure using x-ray fluorescence, x-ray diffraction and field emission scanning electron microscope. The effect of soluble silica was evaluated based on these properties. Various level of replacement (0-10%) was used in this study. Fresh and hardened mortar performance was evaluated via compressive strength, porosity, heat of hydration, thermogravimetry and microstructure analysis. The treated ash obtained with optimum parameters has exhibited significantly lower amount of metals. The amounts of metals leached out correlates with the significant increment of silica content compared with raw ash. Transformation of treated CBA into soluble form has offered a positive contribution to the properties of mortar binder in cementitious system which was evidenced by strength activity index value than untreated and treated mortar specimen. In this study, 5% of soluble silica was found as the optimum cement replacement that shows significant strength increment from early and later age. Refinement of microstructure after soluble silica inclusion by secondary Calcium- Silicate- Hydrate (C-S-H) was found scattered on the surface of cement particles with compact and reticular microstructure closely interweaving with each other in forming continuous structure. This microstructure reformation have effectively strengthen the bonding and filled the micro pores of cement matrix and improved the macro strength performance. Statistical analysis using pearson correlation coefficients shows the potentially important correlation between the compressive strength performances and the independent variables of porosity, addition of silica content, surface area, unit weight and higher removal of aluminum oxide. From this study, coal bottom ash shows a positive prospect to be developed as an alternative pozzolan after pre-treatment process. It would also assist in the green disposal of this scheduled waste.